Temple and empire: the context of the temple piety of Luke-Acts - Monier, Mina (Lexington Books/Fortress Academic, 2021)
"Temple and Empire explores the theme of temple piety in Luke-Acts and 1 Clement in historical context. Mina Monier argues that situating both works in Trajanic Rome, and reading them through the lens of Roman imperial ideology explains their peculiarly positive presentation of the Temple as a form of reverence toward ancient worship and ancestral customs that would not offend, but would appeal to traditional Roman sensibilities."